1999
DOI: 10.1081/ddc-100102226
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Adhesion Testing of Mucoadhesive Drug Delivery Systems

Abstract: Bioadhesive tablets were prepared by physical mixing of polymers and drug, then granulating and compressing into a tablet. The mucoadhesion was evaluated by shear stress measurement, detachment force measurement, and X-ray photography of the rabbit gastrointestinal tract. The strong interaction between the polymer and the mucous lining of the tissue helps increase contact time and permit localization. Polymers like hydroxypropyl methylcellulose K4M (HPMC K4M), hydroxypropyl methylcellulose 100 cps (HPMC 100 cp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Mucoadhesive strength was determined from the ex-vivo study for assurance of adherence. From the literature, it has been found that HPMC K4M has maximum mucoadhesive strength (due to more hydroxyl groups) followed by Carbopol [41]. In comparison with the second half of the DDS, the first part (T1F1) had less coating polymer applied to it (T2F3).…”
Section: Discussionmentioning
confidence: 99%
“…Mucoadhesive strength was determined from the ex-vivo study for assurance of adherence. From the literature, it has been found that HPMC K4M has maximum mucoadhesive strength (due to more hydroxyl groups) followed by Carbopol [41]. In comparison with the second half of the DDS, the first part (T1F1) had less coating polymer applied to it (T2F3).…”
Section: Discussionmentioning
confidence: 99%
“…During the erosion of the formulations, they can help to prolong the retention time of the systems in the periodontal pockets. HPMC is often used as a mucoadhesive agent in oral formulations such as films [24] or buccal tablets [25] to increase the residence time of the delivery system, while ZnHA is regularly applied in topical gels to accelerate the healing of wounds of different etiologies and to decrease the chance of a possible bacterial superinfection [26], or may be used as a mucoadhesive agent in ophthalmic solutions to lengthen clearance and provide higher efficiency [27].…”
Section: Methodsmentioning
confidence: 99%
“…Methocel E4M (hydroxypropyl methylcellulose, HPMC) was used as a gelling and mucoadhesive component. HPMC is often used as a mucoadhesive agent in oral formulations such as films [110] or buccal tablets [111] to increase the residence time of the delivery system.…”
Section: Materials Used For the Lipid-based Systemsmentioning
confidence: 99%